The Geneva Convention on Laws of War and the Sudan Armed Conflict - Osimen Goddy Uwa; Moyosoluwa Dele- Dada (Ridwan Institute, 2023)
The Geneva Convention contains regulations that govern the conduct of war and the treatment of individuals affected by war. However, despite the existence of this regulation created to guide the conduct of hostilities and protect civilians in international and non-international armed conflict, there are still recorded cases of actions by state and non-state actors that run contrary to the dictates of the convention. Records show that in modern day conflict, indiscriminate attacks and the use of unauthorized weapons are still being launched against civilian population, recruitment of child soldiers in insurrections, the use of weapons with indiscriminate effects, genocide, among others. It is against this backdrop that this paper examined the Sudan conflict and the application of the Geneva Convention on the laws of war. From the findings, a wide range of violation of the dictate of the Geneva Convention in the Sudan conflict was observed. The paper concludes that while the Geneva Convention continues to be relevant today, its provisions are still violated in modern day conflict such as Syria, Yemen, and Myanmar. The international community must continue to uphold the principles of the convention and hold those who violate it accountable.